2013
DOI: 10.2478/eko-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Serbian spruce (Picea omorica/Panc./Purkyne) variability in the artificial populations in Serbia

Abstract: Isajev V., Lavadinović V., Lučić A., Rakonjac L.J.: Serbian spruce (Picea omorca /Panc./ Purky ne) variability in the artificial populations in Serbia. Ekológia (Bratislava), Vol. 32, No. 3, p. 277-282, 2013. A great part of the genetic variation and the potentials of Serbian spruce natural populations have been incorporated in several plantations in the Western Serbia at the site Quercetum fraineto-cerris s.l., Salicetum fragillis s.l and Pinetum nigre s.l. and in other similar occurrences In this way, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In the case of Serbia, reforestation is believed to have started as early as the 19th century CE but coniferization of broadleaved forests became a common practice only post World War II (Rakonjac and Nevenic, 2012). From thereon, Austrian pine (Pinus nigra L.) is reported to have been favored for both the submontane-montane beech sites in beech coppice forests as well as unforested areas that are characterized by xerothermic conditions and degraded soils (Isajev et al, 2009); Pinus nigra L. is present in the vegetation surrounding the study site. Hence, significant growth of Pinus in the late LIA period might have both natural (availability of moisture in the montane region) and human intervention as causal factors.…”
Section: Ecological Changes During 1720e1850 Ce (Late Lia)mentioning
confidence: 99%
“…In the case of Serbia, reforestation is believed to have started as early as the 19th century CE but coniferization of broadleaved forests became a common practice only post World War II (Rakonjac and Nevenic, 2012). From thereon, Austrian pine (Pinus nigra L.) is reported to have been favored for both the submontane-montane beech sites in beech coppice forests as well as unforested areas that are characterized by xerothermic conditions and degraded soils (Isajev et al, 2009); Pinus nigra L. is present in the vegetation surrounding the study site. Hence, significant growth of Pinus in the late LIA period might have both natural (availability of moisture in the montane region) and human intervention as causal factors.…”
Section: Ecological Changes During 1720e1850 Ce (Late Lia)mentioning
confidence: 99%
“…The ndings underscored that genetic variability was far greater than what could be inferred from mere observations of morphological variability in parent trees. Isajev (1987) analyzed the individual variability of several trees from three planted forests of Serbian spruce in Serbia. Morphometric analysis of 1.000 cones harvested in 1981 and 1983 showed the existence of spontaneous individual variability between trees for length, width, and number of grains per cone, while the shape of the cone was signi cantly less variable.…”
Section: Principal Components Analysis (Pca) For Measured Traitsmentioning
confidence: 99%
“…The range of variability for the length of cones was, on average, from 20 to 70 mm, for widths from 10 to 23 mm, while the mean number of grains varied from 20 to 113 per cone. The size of the cone in the same tree varied within 5% between different harvest years, which indicates strong genetic control of this trait (Isajev 1987). The obtained results showed that the Serbian spruce seeds from all three planted forests are characterized by very good quality (average germination rate was 90%).…”
Section: Principal Components Analysis (Pca) For Measured Traitsmentioning
confidence: 99%
“…Schwerin (1929in Vidaković 1991 described two varieties of Picea omorika: the variety serbica Schwer., with short branches and a narrow pyramidal crown growing in its native range, and the cultivated variety P. omorika borealis, with a broader crown occurring outside the range of its original distribution. Isajev (1987) and Milovanović (2007) described these and four other varieties of Picea omorika. Vidaković (1991) considers these varieties, except the serbica variety, as horticultural forms or cultivars.…”
Section: Taxonomymentioning
confidence: 99%